Gambaran Mutu Makanan Pada Penderita Autisme Di Panti Asuhan Al-Rifdah Semarang - Dwi Septi Ambarwati; Ali Rosidi; Yuliana Noor SU (Universitas Muhammadiyah Semarang, 2014)
The quality of the food is served judging the quality of the consumer to be aware of the color, texture, aroma, flavor, and sanitation on the equipment used. In children with autism need to be considered in the therapeutic quality food using free gluten and free casein. The purpose of this study was to determine the picture quality of food in people with autis in the orphanage Al-Rifdah Semarang. Type of study used descriptive and cross-sectional methods. Population and samples taken in this study is a food that is served in Al-Rifdah Orphanage Semarang for 4 days. Primary data include type of foods that contain gluten and casein, heavy foods containing gluten and casein. Secondary data include a general description of the profile Orphanage Al-Rifdah Semarang. Data collected edited and processed and analyzed with descriptive analysis using nutrisurvey program. From the research that has been done of children with autism who live in the orphanage Al-Rifdah Semarang by 11 children aged 5 to 19 years. With male gender as much as 9 children and female sex as much as 2 children. Orphanage in Al-Rifdah Semarang still serving food sources of gluten in any menu. With an average of 715.24 in the one-day gr ingredients are gluten-containing foods, and the average in a day are 19.98 grams of foods that contain casein.